Design, Synthesis, Biological Evaluation, and In Silico ADMET Studies of 1,8-Naphthyridine Derivatives as an H1-receptor Inhibitor: Design, Synthesis, Biological Evaluation, and In Silico ADMET Studies of 1,8-Naphthyridine Derivatives as an H1-receptor Inhibitor - Pal, Dr. Dilipkumar (International Journal of Pharmaceutical & Biological Archive, 2019)
In the present study, 1,8-naphthyridine-3-carboxylic acid derivatives (5a1, 5a2, 5b1, and 5b2) were designed, synthesized, and screened for their in vitro H1-antihistaminic activity. H1R inhibitory activity of the synthesized derivatives was calculated by the modified Van Arman technique, histamine-induced bronchoconstriction in guinea pigs. A good bronchorelaxant effect of compounds was observed in histamine-contracted guinea pig tracheal chain through H1-receptor antagonism. In addition, the hypothetically resulted compounds are checked for their reliability on other in silico drug designing online web services like SwissADME predictor. In silico ADMET analysis results show that all the derivatives had negligible toxicity, good absorption, and solubility profile. These compounds may serve as possible lead for establishing safe and effective antihistaminic agent(s).